An Early Investigation into Possible Alternatives to Stapled Hysterotomy in Open Fetal Surgery - Church, Joseph T.; McLeod, Jennifer S.; Coughlin, Megan A.; Bergin, Ingrid L.; Perkins, Elena M.; Hoffman, Hayley R.; Bilger, Mark; Rojas-Peña, Alvaro; Treadwell, Marjorie C.; Berman, Deborah R.; Jarboe, Marcus D.; Mychaliska, George B.; Perrone, Erin E. (American Journal of Perinatology, 2019)
Purpose We hypothesized that surgical energy could be used to create hysterotomies in open fetal surgery.Study Design Initial studies compared the LigaSure Impact and Harmonic ACE + 7 Shears in the efficiency of hysterotomy and thermal damage. Pregnant ewes at an estimated gestational age (EGA) of 116 to 120 days (term = 145; n = 7) underwent hysterotomy using either device. Hysterotomy edges were resected, and thermal injury extent was determined by histopathological assessment. Upon determining a superior device, subsequent studies compared this to the AutoSuture Premium Poly CS*-57 Stapler in uterine healing. Pregnant ewes (n = 6) at an EGA of 87 to 93 days underwent 6-cm hysterotomy in each gravid horn with either the stapler (n = 5) or Harmonic (n = 5) followed by closure and animal recovery. After 37 to 42 days, uterine healing was assessed by evaluating tensile strength and histopathology.Results Thermal damage was more extensive with the LigaSure (n = 11 hysterotomies) than with the Harmonic (n = 11; 5.6 ± 1 vs. 3.1 ± 0.6 mm; p < 0.0001);therefore, the Harmonic was selected for healing studies. Gross scar appearance and tensile strength were the same between the Harmonic and stapler. The stapler caused more fibrosis (4/7 samples with “moderate” fibrosis vs. 0/8 with the Harmonic; p = 0.02).Conclusion The Harmonic ACE + 7 caused less thermal injury than the LigaSure Impact and performed similar to the CS*-57 Stapler in uterine healing with continued gestation.
Keywords: hysterotomy; prenatal; Harmonic; LigaSure; AutoSuturePremium Poly CS*-57 Stapler; surgical energy